Network selection algorithm based on synergetic for heterogeneous wireless network - Ran LUO; Su ZHAO; Qi ZHU (Dianxin kexue)
A network selection algorithm based on synergetic for heterogeneous wireless network was proposed. The algorithm considered the network selection as a systematic problem. The optional network was a composite system and each kind of service running on the terminal was a subsystem. The entropy of the composite system was obtained according to the concept of entropy and it can reflected the degree of coordination among the subsystems, which in turn reflected the overall performance of the network. The simulation results show that the QoS satisfaction rate of services based on the proposed algorithm is 95%, while the QoS satisfaction rate of services based on the TOPSIS algorithm is only 25%, and the performance of the former is improved by nearly four times, indicating that the problem of multi-service terminal network selection can be solved by the proposed algorithm.